Sp3-cificity of TNF-α expression promotes the Smac mimetic-mediated killing of cancer cells. (4th July 2019) - Beug, Shawn T.; Korneluk, Robert G.; LaCasse, Eric C.
ABSTRACT: A genome-wide small-interfering RNA-based screen identified the transcription factor Specificity Protein 3 (SP3) as a critical factor for Second mitochondrial-derived activator of caspase (Smac) mimetic-mediated killing of cancer cells. In concert with Nuclear Factor kappa B (NF-κB, ) SP3 is required for the expression of the cytokine Tumor Necrosis Factor alpha (TNF-α) under basal and Smac mimetic-stimulated conditions.